Thermodynamics and kinetics of early stages of carbon dot formation: a case of citric acid and ethylenediamine reaction - Pykal, Martin; Nociarová, Jela; Řeha, David; Filo, Juraj; Šebela, Marek; Zajíček, Petr; Paloncýová, Markéta; Olla, Chiara; Mocci, Francesca; Cappai, Antonio; Carbonaro, Carlo Maria; Baďura, Zdeněk; et al. (Nanoscale, 2025)
Owing to their extraordinary photophysical properties, carbon dots (CDs) have found applications across various fields, including bioimaging, sensing, and environmental research. Despite huge application potential, the fabrication of CDs still lacks the desired control at the molecular level, and precise structural regulation towards property-tailored CDs remains elusive. The mechanistic details of nucleation, growth, and carbonization processes leading to CDs are still unknown, with key thermodynamic and kinetic parameters yet to be revealed. Herein, we performed quantum chemical calculations of explicitly micro-hydrated reaction systems to thoroughly explore the mechanism of a prototypical reaction of citric acid and ethylenediamine. The theoretical results showed activation barriers and thermodynamics along the reaction pathway, thus helping identify key heterocyclic intermediates and cyclization products. The cyclization and condensation reactions were further simulated via a reactive molecular dynamics protocol, suggesting potential growth scenarios and generating plausible structures for further exploration of the polymerization and carbonization processes. The theoretical calculations were cross-validated with NMR and MALDI-TOF measurements. The data obtained provide a comprehensive deterministic insight into the initial stages of CD formation, revealing new reaction intermediates and pathways, and rationally predicting the formation of specific structural arrangements of premature CDs. The presented deterministic approach represents an important step towards rational bottom-up design of these unique fluorescence systems.